Sustainability Reporting Practice in Technology Companies in ASEAN: a Systematic Literature Review - Tomy Rizky Izzalqurny; Tatas Ridho Nugroho; Adrian Hartanto Darma Sanputra; Arika Miladia (Universitas Muhammadiyah Semarang, 2026)
This study conducts a comprehensive Systematic Literature Review (SLR) to examine sustainability reporting (SR) practices among technology companies in the ASEAN region. Guided by the PRISMA 2020 protocol, the review synthesizes results from 11 peer-reviewed journal articles published between 2015 and 2025. The research aims to map SR practices, analyze links between SR, governance, innovation, and performance, and identify new challenges and research gaps in sustainability reporting. The findings show that SR implementation in ASEAN remains fragmented and mostly voluntary. Disclosure quality varies across countries. Governance factors such as board independence, gender diversity, and sustainability commitment enhance the credibility and clarity of SR. Strong institutional frameworks in Malaysia and Singapore foster more robust adoption. Digital transformation and sustainability-driven innovation help boost reporting efficiency and transparency for stakeholders. However, institutional and technological barriers limit broader adoption. Compared to Europe and China, ASEAN lacks regulatory harmony, data standards, and digital readiness. This study adds value by consolidating theories, such as Stakeholder Theory, Legitimacy Theory, and the Resource-Based View. It explains how governance and innovation shape the development of SR in emerging digital economies. The review concludes by calling for standardization across ASEAN countries, capacity-building efforts, and more longitudinal empirical studies. These steps can strengthen SR’s strategic impact on sustainability and accountability in ASEAN’s technology sector.